The Twenty-First-Century Avengers: Exploration of War, Globalization, and Identity Politics - Acosta Bustamante, Leonor (REDEN. Revista Española de Estudios Norteamericanos, 2023)
The economic and cultural impact of the four films forming the saga of The Avengers from 2012 to 2019 stands for the impressive accumulation of superhero fiction in the 21st century, with a remarkable resituation of the topic of war conflict into the popular imagination quite affected by the traumatic beginning of the era in the New York scenario on 9/11. This article intends to analyze the different plot elements in The Avengers (2012), The Avengers. Age of Ultron (2015), The Avengers. Infinity War (2018), and The Avengers. Endgame (2019) to find clues to explain how the Marvel Cinematic Universe accomplishes a complex exploration of the nature of war, and how the films offer new ways of deconstructing simplistic Manichean polarization between good vs. evil. With this objective in mind, the study pays attention to how this deconstruction also needs to concentrate on the decomposition of stereotypes related to identity politics.